2021
DOI: 10.1136/jech-2020-214257
|View full text |Cite
|
Sign up to set email alerts
|

Green spaces, subjective health and depressed affect in middle-aged and older adults: a cross-country comparison of four European cohorts

Abstract: BackgroundStudies on associations between urban green space and mental health have yielded mixed results. This study examines associations of green space exposures with subjective health and depressed affect of middle-aged and older adults in four European cohorts.MethodsData came from four Western-European and Central-European ageing cohorts harmonised as part of the Mindmap project, comprising 16 189 adults with an average age of 50–71 years. Green space exposure was based on the distance to the nearest gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
2
1
Order By: Relevance
“…In contrast to the expectation that more NDVI mitigates depression ( 19 , 48 ), the association failed to reach statistical significance in this study, which is consistent with some other previous findings ( 20 , 54 ). Similar to prior studies ( 33 , 69 ), however, more scattered trees within campuses helped to protect against depression.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast to the expectation that more NDVI mitigates depression ( 19 , 48 ), the association failed to reach statistical significance in this study, which is consistent with some other previous findings ( 20 , 54 ). Similar to prior studies ( 33 , 69 ), however, more scattered trees within campuses helped to protect against depression.…”
Section: Discussionsupporting
confidence: 83%
“…Empirical evidence on impact of NDVI on depression is conclusive ( 19 , 20 , 54 ); however, which type of green space has a greater effect on depression is not yet well-understood ( 30 , 31 ). In this paper, we focus on the benefits of NDVI and five types of urban natural features (i.e., dense tree, scattered trees, bush/scrubs, low plants, and water) derived from local climate zone maps, for the reduction of depression.…”
Section: Methods and Datamentioning
confidence: 99%
“… 1 2 5–12 In line with our results for the association between nature exposure and mental health, in a survey across 18 countries (n=16 703), no clear associations were observed between green or blue space exposure indicators and antidepressive or anxiety medication use, 31 and in a cross-sectional study of ageing cohorts in four European studies (n=16 189), no association between distance to the nearest green space and self-reported depressed affect was observed. 32 In contrast to our results, a recent longitudinal study from Finland (n=19 851) observed an association between high residential greenness and low risk of doctor-diagnosed depression 33 ; however, no information on visits to green space were used. Contrary to our results, a Spanish cross-sectional study (n=958) found that surrounding greenness was associated with decreased odds of self-reported benzodiazepine use.…”
Section: Discussioncontrasting
confidence: 99%
“…10,12,13 Recent longitudinal studies showed an inverse association between greenness and depression, but systematic reviews are inconclusive. 81–83 In a previous study greenness was associated with a positive change in the emotional component of health-related quality of life among CABG patients, but no association was found with the physical or the social component. 58 Analyses of pathophysiologic pathways show greenness to associate with lower levels of sympathetic activation, reduced oxidative stress, higher angiogenic capacity, and lower inflammation levels linked with cardiovascular disease, depression and premature mortality.…”
Section: Discussionmentioning
confidence: 87%